The effect of Lu AG09222 on PACAP38- and VIP-induced vasodilation, heart rate increase, and headache in healthy subjects: an interventional, randomized, double-blind, parallel-group, placebo-controlled study - Rasmussen, Nadja Bredo; Deligianni, Christina; Christensen, Casper Emil; Karlsson, William Kristian; Al-Khazali, Haidar Muhsen; Van de Casteele, Tom; Granhall, Charlotte; Amin, Faisal Mohammad; Ashina, Messoud (Journal of headache and pain, 2023)
Background Pituitary adenylate cyclase-activating polypeptide (PACAP), structurally related to vasoactive intestinal peptide (VIP), is one of the important mediators in the pathogenesis of migraine and is known to dilate cranial arteries and induce headache and migraine. Our objective was to determine whether Lu AG09222—an investigational humanized monoclonal antibody directed against PACAP ligand—would inhibit the PACAP-signaling cascade by abolishing its vasodilatory and headache-inducing abilities. Methods In a randomized, double-blind, parallel-group, single-dose, placebo-controlled study of Lu AG09222, healthy volunteers aged 18–45 years without history of headache disorders were randomly allocated to three treatment sequences (1:2:2) on two experimental infusion visits with 9 ± 3 days’ interval: placebo + saline + saline ( n = 5), placebo + PACAP38 + VIP ( n = 10), and Lu AG09222 + PACAP38 + VIP ( n = 10). The primary outcome measure was area under the curve (AUC) of the change in superficial temporal artery (STA) diameter from 0 to 120 min after start of infusion of PACAP38. The study was conducted at the Danish Headache Center in Copenhagen, Denmark. Results In participants who received Lu AG09222 + PACAP38 infusion, there was a significantly lower STA diameter (mean (SE) [95% CI] AUC ‒35.4 (4.32) [‒44.6, ‒26.3] mm × min; P < 0.0001) compared to participants who received placebo + PACAP38 infusion. Secondary and explorative analysis revealed that PACAP38 infusion induced an increase in facial blood flow, heart rate and mild headache, and indicated that these PACAP38-induced responses were inhibited by Lu AG09222. Conclusions This proof-of-mechanism study demonstrated that Lu AG09222 inhibited PACAP38-induced cephalic vasodilation and increases in heart rate, and reduced concomitant headache. Lu AG09222 may be a potential therapy against migraine and other PACAP-mediated diseases. Trial registration ClinicalTrials.gov: NCT04976309. Registration date: July 19, 2021. Graphical Abstract